Efficient, rapid and incremental extraction of bioactive compounds from the flowers of Hibiscus manihot L. - Juzhao Liu; Yujie Fu; Qi Cui (Beverage Plant Research)
Flavonoids are the primary functional components in the flowers of Hibiscus manihot L. (HMLF). In this study, an efficient and green ionic liquid-high-speed homogenization coupled with microwave-assisted extraction (IL-HSH-MAE) technique was firstly established and implemented to extract seven target flavonoids from HMLF. Single-factor experiments and Box-Behnken design (BBD) were utilized to maximize the extraction conditions of IL-HSH-MAE, which were as follows: 0.1 M of [C4mim]Br, homogenate speed of 7,000 rpm, homogenate time of 120 s, liquid/solid ratio of 24 mL/g, extraction temperature of 62 °C and extraction time of 15 min. The maximal total extraction yield of seven target flavonoids attained 22.04 mg/g, which was considerably greater than the yields obtained by IL-HSH, IL-MAE, 60% ethanol-HSH-MAE and 60% ethanol-MAE. These findings suggested that the IL-HSH-MAE method can be exploited as a rapid and efficient approach for extracting natural products from plants. The process also possesses outstanding superiority in being environmentally friendly and having a high extraction efficiency and is expected to be a luciferous prospect extraction technology.